Estudo do estado trófico do reservatório Acarape do Meio mediante a determinação de indicadores de qualidade de água - Ribeiro, Irla Vanessa Andrade de Sousa (2007)
The process of storage of water in semi-arid regions has become a considerable way of reducing the shortage of this natural resource. Like this, it is common in areas with characteristics of the Brazilian Northeast, the construction of great reservoirs that has been being to assist, with certain regularity, demands for the most several uses. On the other hand, the storage of water in reservoirs bring some vulnerabilities to the water, concerning with the degradation risk. As it is known, the stored water is subject to long residence times, allowing the appearance of some important chemical and biological reactions. These reactions, associated with some sewage releases, that come from urban, industrial, and rural areas, promote the accelerating the process of aging of the reservoirs, known as Eutrophication Process, that depends, fundamentally, of the presence of nutrients inside the reservoirs. This work studied, through field data, associated with a methodology of calculation of Modified Trophic State Index and the Water Quality Index, the environmental conditions of the Acarape do Meio Reservoir, in the State of Ceará, trying to identificaty the main transformations in their trophic levels, as well as, the identification of the main causes of a possible process of eutrophization of it. The data cover the years 2001 through 2006. With that, it was possible to know the characteristics concerning with the stratification this body of water, with respect to temperature and the chemical process. Also, considering the several points of collections of data, it was possible to present results concerning with the Trophic State Index and the Water Quality Index, a long of the all surface of the reservoir, showing, like this, the several critical points of it. With respect to the Trophic Level Index, two calculations were used, being for the first used, just, the chlorophyll a and the phosphors, while in the second calculation they were used, besides those two substances, the present soluble orthophosphate in those waters. The results show that there is a strong variability of the quality of the waters of this reservoir, but that, in the years of 2004 and 2005, their waters reached a hipereutrophic level, that represents the presence of a fort presence of nutrients coming of the entrances of the reservoir and, probably, of the rural areas that exist around the it. The results showed yet, even if the vertical variation of temperature is not so significant inside the reservoir, there is a strong presence of chemical stratification in the deepest layers of this body of water.